A negative electrode material and preparation method thereof, a negative electrode sheet and a lithium ion battery
By using a porous framework and alternately deposited silicon-carbon composite layer structure in lithium-ion batteries, the performance attenuation problem caused by volume changes during charging and discharging of silicon negative electrodes is solved, and higher structural stability and cycle life are achieved.
Patent Information
- Application Number
- CN202211739522.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-12-30
AI Technical Summary
In existing lithium-ion batteries, the silicon negative electrode has a particle powder during the charging and discharging process, and the active substances are repeatedly grown from the conductive network and the surface SEI film due to volume changes, resulting in attenuation of cyclic performance and expansion of thickness, and poor conductivity of electrons and ions, which limits its application.
Porous skeleton material is used as the core, and the pores are reserved as the volume expansion space during the charge and discharge of the silicon layer. By alternately deposition of the silicon material layer and the carbon material layer multiple times, the coating integrity of the silicon is improved, the side reactions of electrolyte contact are reduced, and a porous carbon coating layer is provided on the outer layer to protect the silicon material.
It effectively avoids the cracking and separation of the silicon layer, reduces the volume expansion of the negative electrode material, improves structural stability and cycle life, and enhances the conductivity and rate performance.
Smart Images

Figure CN116093287B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a negative electrode material and a preparation method thereof, a negative electrode sheet and a lithium-ion battery. Background Art
[0002] The rapid development of new energy technologies such as portable electronic products, electric vehicles, and energy storage power stations has put forward higher requirements for the energy density of batteries, but the theoretical lithium storage capacity of existing graphite negative electrodes is low, which seriously restricts the further improvement of the energy density of lithium-ion batteries. Silicon has a theoretical specific capacity ten times that of graphite and is an ideal negative electrode for the next generation of high-energy-density lithium-ion batteries. However, the silicon negative electrode involves huge volume changes during the charging and discharging process, which can easily cause problems such as particle pulverization, separation of active substances from the conductive network, and repeated growth of the surface SEI film, resulting in rapid attenuation of the battery's cycle performance or large thickness expansion; in addition, silicon is a semiconductor material with poor electronic and ionic conductivity, resulting in a low power density of silicon materials. These problems have seriously restricted the actual application of silicon negative electrodes.
[0003] In response to the above problems, CN 106384825 A proposes to use carbon nano-silicon, graphite and organic carbon to form silicon-carbon composite microsphere negative electrode materials, so as to avoid direct contact of nano-silicon with electrolyte during the cycle process to improve efficiency. At the same time, the entire silicon-based negative electrode is coated with carbon to form a good electron conduction path, which can improve the cycle performance of the material to a certain extent. However, in the cycle process, silicon is not given expansion space, and the silicon core expands and undergoes volume deformation, so that the carbon coating layer is prone to produce pores or cracks, and the electrolyte will enter these pores or cracks, and reduce and decompose to produce new passivation film when the negative electrode is at a lower potential. As the charge and discharge process continues, the carbon coating layer or passivation film will continue to crack and expose new sites, so that the passivation film will grow repeatedly, continuously consuming the active lithium ions in the battery, causing the continuous attenuation of the battery capacity and increasing the thickness of the battery.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first object of the present invention is to provide a negative electrode material, which uses a porous skeleton material as a core. The pores reserved in the porous skeleton reserve space for the volume expansion of the silicon layer during the charge and discharge process, thereby avoiding the rupture and separation of the silicon layer, and reducing the volume expansion of the negative electrode material, thereby ensuring the structural stability of the negative electrode material. In addition, the silicon material layer and the carbon material layer deposited alternately for multiple times effectively improve the coating integrity of the silicon, reduce the side reactions of the silicon layer rupture and the contact with the electrolyte, and avoid the consumption of the electrolyte, thereby helping to improve the cycle life of the battery.
[0006] The second object of the present invention is to provide a method for preparing the negative electrode material, wherein silicon source gas and carbon source gas are deposited in the porous carbon pores by high temperature deposition, and a cyclic deposition layer of silicon and carbon is formed in the porous carbon pores to obtain the negative electrode material. The preparation method of the present invention has the advantages of simple process, easy operation, and easy process production.
[0007] The third object of the present invention is to provide a negative electrode plate comprising the above-mentioned negative electrode material, which overcomes the disadvantage of silicon being easily expanded and deformed during charging and discharging, and also overcomes the problem of low energy density of pure carbon materials.
[0008] A fourth object of the present invention is to provide a lithium-ion battery comprising the above-mentioned negative electrode plate.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] A negative electrode material provided by the present invention comprises a porous skeleton and at least two silicon-carbon composite material units arranged in the porous skeleton;
[0011] Each of the silicon-carbon composite material units comprises a silicon material layer and a carbon material layer which are sequentially connected;
[0012] A modified layer is further included between the two silicon-carbon composite material units, and the modified layer includes at least one of carbon nanotubes, graphene, graphene oxide, metal or metal alloy.
[0013] Preferably, the number of the silicon-carbon composite material units is 2 to 6.
[0014] Preferably, the total thickness of all the silicon-carbon composite material units is 1-80 nm.
[0015] Preferably, the mass fraction of silicon in the silicon-carbon composite material unit is 1% to 60%.
[0016] Preferably, the pore size D of the porous skeleton is 50 =50~600nm.
[0017] Preferably, the specific surface area of the porous skeleton is 100-1500m 2 / g.
[0018] Preferably, the porous skeleton comprises at least one of porous carbon, porous ceramic, porous metal or alloys thereof.
[0019] Preferably, the porous skeleton further includes a doping element, and the doping element includes at least one of nitrogen, phosphorus, silicon, germanium, tin, boron, aluminum, boron, gallium, and indium.
[0020] Preferably, the porosity of the porous skeleton is 10% to 90%.
[0021] Preferably, the particle size D of the porous skeleton is 50 =2~40μm.
[0022] Preferably, a modified layer is further included between the two silicon-carbon composite material units.
[0023] Preferably, the modified layer comprises at least one of carbon nanotubes, graphene, graphene oxide, metal or metal alloy.
[0024] Preferably, the thickness of the modified layer is 0.2-10 nm.
[0025] Preferably, the silicon material layer includes at least one of elemental silicon, silicon-boron material, silicon-carbon material and silicon-oxygen material.
[0026] Preferably, the carbon material layer is obtained by vapor deposition using a gaseous carbon source.
[0027] Preferably, the outermost layer of the negative electrode material is also provided with a porous carbon coating layer.
[0028] Preferably, the porosity of the porous carbon coating layer is 1% to 20%.
[0029] Preferably, the thickness of the porous carbon coating layer is 0.1-3 μm.
[0030] The method for preparing the negative electrode material provided by the present invention comprises the following steps:
[0031] (a), obtaining a porous skeleton;
[0032] (b), depositing a silicon material layer;
[0033] (c), depositing a carbon material layer;
[0034] (d) preparing a modified layer;
[0035] Repeat steps (b) and (c) at least once.
[0036] Preferably, step (b) and step (c) are repeated 1 to 5 times, that is, after the first unit is deposited, the modified layer is coated, and then silicon material layers and carbon material layers are alternately deposited.
[0037] Alternatively, step (b), step (c) and step (d) are repeated 1 to 5 times, that is, after the first unit is deposited, the modified layer is coated, and then the silicon material layer, the carbon material layer and the modified layer are alternately deposited.
[0038] Preferably, after the last deposition of the silicon-carbon composite material unit, the method further comprises: (e) depositing a porous carbon coating layer.
[0039] Preferably, in step (b), the gaseous silicon source for depositing the silicon material layer comprises at least one of monosilane, disilane, trichlorosilane, silicon tetrafluoride, silicon tetrachloride and silicon dichloride.
[0040] Preferably, in step (b), the deposition temperature of the silicon material layer is 400-900°C.
[0041] Preferably, in step (b), the deposition time of the silicon material layer is 0.5 to 50 hours.
[0042] Preferably, in step (b), the flow rate of the gaseous silicon source is 0.02 to 20 L / min.
[0043] Preferably, in step (b), the deposition pressure of the silicon material layer is 0.1-5 MPa.
[0044] Preferably, in step (c), the gaseous carbon source for depositing the carbon material layer comprises at least one of ethylene, methane, ethane, propane, acetylene and ethylene.
[0045] Preferably, in step (c), the deposition temperature of the carbon material layer is 400-1500°C.
[0046] Preferably, in step (c), the deposition time of the carbon material layer is 1 to 20 hours.
[0047] The present invention provides a negative electrode plate, comprising the negative electrode material.
[0048] The present invention provides a lithium-ion battery, comprising the negative electrode sheet.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] (1) The negative electrode material provided by the present invention adopts a porous skeleton with a larger pore size, which can alleviate the blockage of surface pores, reduce the deposition of silicon in the inner pores of the porous skeleton, improve the utilization rate of silicon inside the particles, and maintain the microporous structure in the center of the porous skeleton.
[0051] (2) In the negative electrode material provided by the present invention, the pores reserved in the porous skeleton reserve space for the volume expansion of the silicon layer during the charge and discharge process, thereby avoiding the rupture and separation of the silicon layer during the charge and discharge process, suppressing the volume expansion problem of the negative electrode material, and ensuring the structural stability of the negative electrode material.
[0052] (3) The negative electrode material provided by the present invention, by alternately depositing silicon layers and carbon layers multiple times, will effectively improve the silicon coating integrity, reduce the possibility of silicon layer rupture and side reactions caused by contact with the electrolyte, and avoid the consumption of the electrolyte, which helps to improve the cycle life of the battery.
[0053] (4) The negative electrode material provided by the present invention, by alternately depositing silicon layers and carbon layers multiple times, will effectively improve the electron transmission path from silicon to carbon layers during the cycle, thereby improving the conductivity of the negative electrode material; it helps to improve the rate performance of the battery; in addition, the internal pores and external pores in the negative electrode material can absorb the electrolyte, increase the ion conductivity of the electrolyte, and thus improve the rate performance of the negative electrode material.
[0054] (5) The negative electrode material provided by the present invention also adds a modified layer during the alternating process to enhance the electron transfer capability between each silicon-carbon composite material unit.
[0055] (6) The negative electrode material provided by the present invention also includes an outermost porous carbon coating layer to protect the negative electrode material and avoid side reactions that may occur when the silicon material layer contacts the electrolyte.
[0056] (7) The method for preparing the negative electrode material provided by the present invention deposits silicon source gas and carbon source gas in the porous carbon pores by high temperature deposition, forms a cyclic deposition layer of silicon and carbon in the porous carbon pores, and obtains the negative electrode material. It has the advantages of simple process, easy operation, and easy process production. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0058] Figure 1 A schematic diagram of the structure of the negative electrode material provided in an embodiment of the present invention;
[0059] Figure 2 A flow chart of a method for preparing a negative electrode material provided in an embodiment of the present invention;
[0060] Figure 3 This is a test result diagram of the cycle number-capacity retention rate of the negative electrode material provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0061] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0062] The present invention provides a negative electrode material, such as Figure 1 As shown, it includes a porous skeleton and at least two silicon-carbon composite material units arranged in the porous skeleton; each of the silicon-carbon composite material units includes a silicon material layer and a carbon material layer arranged in sequence; the carbon material layer and the silicon material layer are alternately deposited in the porous skeleton. The number of silicon-carbon composite material units is at least two, so that the carbon material layer can protect the silicon material layer.
[0063] In addition, a modified layer is further included between the two silicon-carbon composite material units, and only one modified layer may be included between two of the silicon-carbon composite material units, or one modified layer may be included between every two silicon-carbon composite material units. Further, the modified layer includes at least one of carbon nanotubes, graphene, graphene oxide, metal or metal alloy, and mainly connects the two units to optimize the electron channel.
[0064] In a preferred embodiment, the number of the silicon-carbon composite material units is 2 to 6, for example, 2, 3, 4, 5, or 6.
[0065] In a preferred embodiment, the total thickness of all silicon-carbon composite materials units is 1 to 80 nm, for example, any point value among 1 nm, 3 nm, 5 nm, 7 nm, 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, 24 nm, 25 nm, 28 nm, 30 nm, 33 nm, 36 nm, 39 nm, 40 nm, 45 nm, 50 nm, 55 nm, 58 nm, 60 nm, 62 nm, 64 nm, 66 nm, 70 nm, 75 nm, 78 nm, and 80 nm, or a range value consisting of any two point values.
[0066] In a preferred embodiment, the mass fraction of silicon in the silicon-carbon composite material unit is 1% to 60%, including any point value among 1%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 25%, 30%, 33%, 36%, 40%, 44%, 46%, 50%, 52%, 55%, 58%, and 60%, or a range value composed of any two point values.
[0067] In a preferred embodiment, the pore size D of the porous skeleton is 200 μm, which is 200 μm. The pore size D of the porous skeleton is 200 μm, which is 200 μm. 50 =50-600nm, for example, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 220nm, in a preferred embodiment, the specific surface area of the porous skeleton is 100-1500m 2 / g.
[0068] In a preferred embodiment, the porous skeleton comprises at least one of porous carbon, porous ceramics, porous metals or alloys thereof.
[0069] Further, porous ceramics include but are not limited to one or more of porous alumina, porous zirconia toughened alumina, porous partially stabilized zirconia, porous sintered silicon carbide, sintered silicon nitride, porous cordierite, porous zirconia, porous clay-bonded silicon carbide, and porous silica.
[0070] Porous metal materials include, but are not limited to, porous aluminum, porous steel, porous nickel, porous nickel alloy, porous nickel-manganese alloy, porous titanium, porous copper, porous brass, porous gold, porous silver, porous germanium and one or more other metals that can form a porous structure.
[0071] In a preferred embodiment, the porous skeleton further comprises a doping element to modify its surface, and the doping element comprises at least one of nitrogen, phosphorus, silicon, germanium, tin, boron, aluminum, boron, gallium, and indium.
[0072] In a preferred embodiment, the porosity of the porous skeleton is 10% to 90%, for example, any value among 10%, 12%, 15%, 18%, 20%, 25%, 30%, 33%, 36%, 40%, 44%, 46%, 50%, 52%, 55%, 58%, 60%, 65%, 69%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 90% or a range consisting of any two value points.
[0073] In a preferred embodiment, the particle size D of the porous skeleton is 50=2~40μm, for example, any point value among 2μm, 8μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 38μm, 40μm, or a range value consisting of any two point values.
[0074] In a preferred embodiment, the thickness of the modified layer is 0.2 to 10 nm, for example, any point value among 0.2 nm, 0.5 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 9.5 nm, and 10 nm, or a range value consisting of any two point values.
[0075] In a preferred embodiment, the silicon material layer includes at least one of elemental silicon, silicon-boron material, silicon-carbon material and silicon-oxygen material.
[0076] In a preferred embodiment, the carbon material layer is obtained by vapor deposition using a gaseous carbon source. Although the modified layer also includes carbon type modifications, the carbon material layer of the present application is mainly obtained by vapor deposition of a gaseous carbon source and belongs to a hard carbon layer. Therefore, the two belong to different types of carbon layers, and there is no problem of unclear protection scope.
[0077] In a preferred embodiment, the outermost layer of the negative electrode material is also provided with a porous carbon coating layer, and the pores in the porous carbon coating layer can store a certain amount of electrolyte and protect the inner silicon material layer to avoid side reactions caused by direct contact with the electrolyte.
[0078] In a preferred embodiment, the porosity of the porous carbon coating layer is 1% to 20%, for example, any point value among 1%, 2%, 5%, 8%, 10%, 12%, 15%, 17%, 18%, 20% or a range value consisting of any two point values.
[0079] In a preferred embodiment, the thickness of the porous carbon coating layer is 0.1-3 μm, for example, any value among 0.1 μm, 0.8 μm, 1 μm, 1.5 μm, 20 μm, 2.5 μm, 3 μm, or a range consisting of any two values.
[0080] The method for preparing the negative electrode material provided by the present invention comprises the following steps:
[0081] (a) obtaining a porous skeleton; (b) depositing a silicon material layer; (c) depositing a carbon material layer; (d) preparing a modified layer;
[0082] In a preferred embodiment, step (b) and step (c) are repeated 1 to 5 times.
[0083] In a preferred embodiment, Figure 2 As shown, after step (c), the method further includes: (d), depositing a modified layer, and repeating steps (b), (c) and (d) 1 to 5 times.
[0084] In a preferred embodiment, after the last deposition of the silicon-carbon composite material unit, the process further includes: (e) depositing a porous carbon coating layer.
[0085] In a preferred embodiment, in step (b), the gaseous silicon source for depositing the silicon material layer includes at least one of monosilane, disilane, trichlorosilane, silicon tetrafluoride, silicon tetrachloride and silicon dichloride.
[0086] In a preferred embodiment, in step (b), the deposition temperature of the silicon material layer is 400-900°C, for example, any point value among 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, and 900°C, or a range consisting of any two point values.
[0087] In a preferred embodiment, in step (b), the deposition time of the silicon material layer is 0.5 to 50 h, for example, any point value among 0.5 h, 1 h, 5 h, 10 h, 15 h, 20 h, 25 h, 30 h, 35 h, 40 h, 45 h, and 50 h, or a range value consisting of any two point values.
[0088] In a preferred embodiment, the method for preparing the modified layer comprises mixing and coating the modified material with the negative electrode material of the deposited silicon-carbon composite material unit, and then sintering the mixture.
[0089] In a preferred embodiment, in step (b), the flow rate of the gaseous silicon source is 0.02 to 20 L / min, for example, any point value among 0.02 L / min, 0.1 L / min, 0.5 L / min, 1 L / min, 5 L / min, 7 L / min, 9 L / min, 10 L / min, 12 L / min, 15 L / min, 18 L / min, and 20 L / min, or a range value consisting of any two point values.
[0090] In a preferred embodiment, in step (b), the deposition pressure of the silicon material layer is 0.1 to 5 MPa, for example, any point value among 0.1 MPa, 0.5 MPa, 1 MPa, 1.5 MPa, 2 MPa, 2.5 MPa, 3 MPa, 3.5 MPa, 4 MPa, 4.5 MPa, and 5 MPa, or a range value consisting of any two point values.
[0091] In a preferred embodiment, in step (c), the gaseous carbon source for depositing the carbon material layer comprises at least one of ethylene, methane, ethane, propane, acetylene and ethylene.
[0092] In a preferred embodiment, in step (c), the deposition temperature of the carbon material layer is 400-1500°C, for example, any point value among 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, and 1500°C, or a range value consisting of any two point values.
[0093] In a preferred embodiment, in step (c), the deposition time of the carbon material layer is 1-20 h, for example, any point value among 1 h, 3 h, 5 h, 7 h, 10 h, 12 h, 15 h, 18 h, 20 h, or a range value consisting of any two point values.
[0094] A negative electrode sheet comprises a negative electrode material, wherein the negative electrode material and a substance comprising a conductive agent and a binder are added to a solvent and mixed to prepare a negative electrode slurry, and then the obtained negative electrode slurry is coated on a negative electrode collector to prepare a negative electrode sheet; the positive electrode slurry is coated on a positive electrode collector to prepare a positive electrode sheet; the positive electrode sheet, a separator and a negative electrode sheet are sequentially stacked or wound to prepare a battery core, and then packaged into a battery.
[0095] The packaging of the present invention includes placing the battery core into a battery housing, welding the cover plate and the battery housing, injecting electrolyte into the battery housing, and forming and sealing the battery. The formation, sealing and other technologies adopt various technologies known to those skilled in the art, and the present invention has no special restrictions.
[0096] The negative electrode current collector, positive electrode slurry, positive electrode current collector, etc. of the present invention are not particularly limited in the present invention, and various negative electrode current collectors, positive electrode slurries, positive electrode current collectors known to those skilled in the art may be used.
[0097] Example 1
[0098] The porous carbon (pore size D50: 200 nm, specific surface area: 905 m 2 / g) was placed in a tube furnace, with an argon flow rate of 0.8L / min and a silane flow rate of 0.5L / min; the deposition temperature was 500°C and the deposition time was 6h. After the silicon layer deposition was completed, the silicon source gas was completely removed, the temperature was raised to 800°C, ethane was introduced for carbon layer deposition, the carbon source flow rate was 0.45L / min, the time was 5h, and the deposition pressure was 0.2kPa, to obtain silicon-carbon material S1.
[0099] The silicon-carbon material S1 and 0.4% carbon nanotube slurry were mixed and stirred for 4 hours, mixed evenly, filtered and dried to obtain the carbon nanotube-modified silicon-carbon material S2.
[0100] S2 was placed in a tube furnace and replaced with inert gas. The flow rate of silane was 0.5 L / min. The deposition temperature was 550°C and the deposition time was 4 hours. After the silicon layer deposition was completed, the gas silicon source was completely removed, the temperature was raised to 850°C, propane was introduced for carbon layer deposition, the carbon source flow rate was 0.45 L / min, the time was 5 hours, and the deposition pressure was 0.2 kPa, and a double-layer silicon-carbon negative electrode material was obtained.
[0101] The specific surface area of the negative electrode material obtained in this example is 17.5 m 2 / g. Through nitrogen adsorption method, it was measured that the negative electrode material had 70% mesopores and 30% micropores; through sulfur-carbon analyzer, it was measured that the mass percentage of silicon element in the negative electrode material was 42.9%.
[0102] Example 2
[0103] The porous copper (pore size D50: 400nm, specific surface area: 509m 2 / g) was placed in a tube furnace with an argon flow rate of 0.8 L / min, and chlorosilane was introduced to deposit a silicon layer with a silicon source flow rate of 0.3 L / min; the deposition temperature was 600°C, the deposition time was 3 h, and the deposition pressure was 0.2 kPa to obtain a silicon-carbon material S1.
[0104] S1 was mixed with 0.1% silver nanowire slurry and stirred for 4 hours, mixed evenly, filtered and dried to obtain carbon nanotube-modified silicon-carbon material S2.
[0105] S2 was placed in a tube furnace, replaced with inert gas, the temperature was raised to 700°C, acetylene was introduced for carbon layer deposition, the carbon source flow rate was 0.4 L / min, the time was 3 h, and the deposition pressure was 0.3 kPa to obtain silicon-carbon material S3. The above deposition steps were repeated 5 times to obtain silicon-carbon negative electrode material.
[0106] The specific surface area of the negative electrode material obtained in this example is 10.3 m 2 / g. The negative electrode material was measured to have 30% mesopores and 70% micropores by nitrogen adsorption method; and the mass percentage of silicon in the negative electrode material was measured to be 35.8% by sulfur-carbon analyzer.
[0107] Example 3
[0108] The porous carbon (pore size D50: 350 m, specific surface area: 697 m 2 / g) was placed in a tube furnace, the argon flow rate was 0.9L / min, tetrasilane was introduced to deposit a silicon layer, and the silicon source flow rate was 0.6L / min; the deposition temperature was 700°C, and the deposition time was 1.5h. After the silicon layer deposition was completed, the gas silicon source was completely removed, the temperature was raised to 900°C, and methane was introduced to deposit a carbon layer, the carbon source flow rate was 0.5L / min, the time was 4h, and the deposition pressure was 0.1kPa. The silicon-carbon material S1 was obtained.
[0109] S1 was mixed with 0.4% conductive silver paste and stirred for 4 hours, mixed evenly, filtered and dried to obtain carbon nanotube-modified silicon-carbon material S2.
[0110] Place S2 in a tubular furnace, introduce inert gas for replacement, raise the temperature to the reaction temperature of silicon source gas deposition, repeat the above steps to deposit silicon layer and carbon layer 4 times, and you can get the silicon-carbon negative electrode material.
[0111] The specific surface area of the negative electrode material obtained in this example is 18.6 m 2 / g. The negative electrode material was measured to have 42% mesopores and 58% micropores by nitrogen adsorption method; the mass percentage of silicon in the negative electrode material was measured to be 39.1% by sulfur-carbon analyzer.
[0112] Example 4
[0113] Porous alumina (pore size D50: 270 nm, specific surface area: 835 m 2 / g) was placed in a tube furnace, chlorosilane was introduced to deposit a silicon layer, the argon flow rate was 0.9L / min, the silicon source flow rate was 0.8L / min; the deposition temperature was 450°C, and the deposition time was 2h. After the silicon layer deposition was completed, the gas silicon source was completely removed, the temperature was raised to 650°C, ethylene was introduced to deposit a carbon layer, the carbon source flow rate was 0.6L / min, the time was 4h, and the deposition pressure was 0.4kPa.
[0114] After the carbon layer deposition is completed, the gaseous carbon source is completely removed, the reaction temperature is lowered to that of silicon source gas deposition, silane is introduced to deposit the silicon layer, and the silicon source flow rate is 0.7L / min; the deposition temperature is 550°C, and the deposition time is 3h. After the silicon layer deposition is completed, the gaseous silicon source is completely removed, the temperature is increased to 750°C, methane is introduced to deposit the carbon layer, the carbon source flow rate is 0.35L / min, the time is 8h, and the deposition pressure is 0.3kPa, and the silicon-carbon material S1 is obtained.
[0115] S1 was mixed with 0.9% graphene slurry and stirred for 4 hours until evenly mixed, filtered and dried to obtain carbon nanotube-modified silicon-carbon material S2.
[0116] Place S2 in a tube furnace, introduce inert gas for replacement, heat up to the reaction temperature of silicon source gas deposition, introduce disilane to deposit the silicon layer, the silicon source flow rate is 0.35L / min; the deposition temperature is 550℃, and the deposition time is 4h. After the silicon layer deposition is completed, wait for the gas silicon source to be completely removed, raise the temperature to 950℃, introduce acetylene for carbon layer deposition, the carbon source flow rate is 0.48L / min, the time is 4h, and the deposition pressure is 0.3kPa. After the carbon layer deposition is completed, the silicon-carbon negative electrode material can be obtained.
[0117] The specific surface area of the negative electrode material obtained in this example is 15.1 m 2 / g. The negative electrode material was measured to have 36.7% mesopores and 63.3% micropores by nitrogen adsorption method; and the mass percentage of silicon in the negative electrode material was measured to be 42.7% by sulfur-carbon analyzer.
[0118] Example 5
[0119] The porous carbon (pore size D50: 340nm, specific surface area: 706m 2 / g, porosity 49%) was placed in a tube furnace, the argon flow rate was 0.58L / min, the silane flow rate was 0.25L / min; the deposition temperature was 500°C, the deposition time was 6h, and the silicon-carbon material S1 was obtained.
[0120] S1 was mixed with 0.7% graphene oxide slurry and stirred for 4 hours until evenly mixed, filtered and dried to obtain carbon nanotube-modified silicon-carbon material S2.
[0121] Place S2 in a tube furnace, introduce inert gas replacement, raise the temperature to 800°C, introduce ethane for carbon layer deposition, the carbon source flow rate is 0.3L / min, the time is 5h, and the deposition pressure is 0.2kPa. Repeat the above deposition steps 4 times to obtain the silicon-carbon negative electrode material.
[0122] The specific surface area of the negative electrode material obtained in this example is 11.8 m 2 / g. The negative electrode material was measured to have 34% mesopores and 66% micropores by nitrogen adsorption method; the mass percentage of silicon in the negative electrode material was measured to be 35.2% by sulfur-carbon analyzer.
[0123] Example 6
[0124] The porous carbon (pore size D50: 230nm, specific surface area: 844m 2 / g) was placed in a tube furnace with an argon flow rate of 1.5 L / min, and chlorosilane was introduced to deposit a silicon layer with a silicon source flow rate of 0.5 L / min; the deposition temperature was 600° C. and the deposition time was 7 h to obtain a silicon-carbon material S1.
[0125] S1 was mixed with 0.6% nano-tin slurry and stirred for 4 hours, mixed evenly, filtered and dried to obtain carbon nanotube-modified silicon-carbon material S2.
[0126] Place S2 in a tube furnace, introduce inert gas replacement, raise the temperature to 700°C, introduce acetylene for carbon layer deposition, the carbon source flow rate is 1L / min, the time is 3h, and the deposition pressure is 0.3kPa. Repeat the above deposition steps 3 times to obtain the silicon-carbon negative electrode material.
[0127] The specific surface area of the negative electrode material obtained in this example is 15.3 m 2 / g. The negative electrode material was measured to have 32% mesopores and 68% micropores by nitrogen adsorption method; and the mass percentage of silicon in the negative electrode material was measured to be 32.1% by sulfur-carbon analyzer.
[0128] Example 7
[0129] The porous carbon (pore size D50: 320nm, specific surface area: 746m 2 / g) was placed in a tube furnace, the argon flow rate was 0.42L / min, tetrasilane was introduced to deposit a silicon layer, and the silicon source flow rate was 0.43L / min; the deposition temperature was 700°C, and the deposition time was 1.5h. After the silicon layer deposition was completed, the gas silicon source was completely removed, the temperature was raised to 900°C, and methane was introduced to deposit a carbon layer, the carbon source flow rate was 0.25L / min, the time was 4h, and the deposition pressure was 0.1kPa, to obtain silicon-carbon material S1.
[0130] S1 was mixed with 0.5% copper nanowire slurry and stirred for 4 hours, mixed evenly, filtered and dried to obtain carbon nanotube-modified silicon-carbon material S2.
[0131] Place S2 in a tubular furnace, introduce inert gas for replacement, raise the temperature to the reaction temperature of silicon source gas deposition, repeat the above steps to deposit silicon layer and carbon layer 3 times, and you can get the silicon-carbon negative electrode material.
[0132] The specific surface area of the negative electrode material obtained in this example is 15.9 m 2 / g. The negative electrode material was measured to have 47% mesopores and 53% micropores by nitrogen adsorption method; and the mass percentage of silicon in the negative electrode material was measured to be 37.1% by sulfur-carbon analyzer.
[0133] Example 8
[0134] The porous carbon (pore size D50: 460nm, specific surface area: 423m 2 / g) was placed in a tube furnace, chlorosilane was introduced to deposit a silicon layer, the argon flow rate was 0.2L / min, the silicon source flow rate was 0.15L / min; the deposition temperature was 450°C, and the deposition time was 2h. After the silicon layer deposition was completed, the gas silicon source was completely removed, the temperature was raised to 650°C, ethylene was introduced to deposit a carbon layer, the carbon source flow rate was 0.15L / min, the time was 4h, and the deposition pressure was 0.4kPa, to obtain a silicon-carbon material S1.
[0135] S1 was mixed with 0.3% carbon nanotube slurry and stirred for 4 hours, mixed evenly, filtered and dried to obtain carbon nanotube-modified silicon-deposited silicon-carbon material S2.
[0136] Place S2 in a tubular furnace, introduce inert gas for replacement, raise the temperature to the reaction temperature of silicon source gas deposition, repeat the above steps to deposit silicon layer and carbon layer 6 times, and you can get the silicon-carbon negative electrode material.
[0137] The specific surface area of the negative electrode material obtained in this example is 8.3 m 2 / g. The negative electrode material was measured to have 12.3% mesopores and 87.7% micropores by nitrogen adsorption method; and the mass percentage of silicon in the negative electrode material was measured to be 39.7% by sulfur-carbon analyzer.
[0138] Example 9
[0139] The porous carbon (pore size D50: 210 nm, specific surface area: 872 m 2 / g,) was placed in a tube furnace, the argon flow rate was 0.28L / min, the silane flow rate was 0.25L / min; the deposition temperature was 500°C, and the deposition time was 6h. After the silicon layer deposition was completed, the silicon source gas was completely removed, the temperature was raised to 800°C, ethane was introduced for carbon layer deposition, the carbon source flow rate was 0.15L / min, the time was 5h, and the deposition pressure was 0.2kPa, to obtain silicon-carbon material S1.
[0140] S1 was mixed with aniline and 1% ammonium persulfate and stirred evenly for 1 hour to obtain a single-layer silicon-carbon material with a polyaniline-coated carbon layer. The silicon-carbon material with a polyaniline-coated carbon layer was placed in a tube furnace, and the silane flow rate was 0.25L / min; the deposition temperature was 550°C, and the deposition time was 4h. After the silicon layer deposition was completed, the gas silicon source was completely removed, the temperature was raised to 650°C, propane was introduced for carbon layer deposition, the carbon source flow rate was 0.15L / min, the time was 5h, and the deposition pressure was 0.2kPa, and the silicon-carbon negative electrode material was obtained.
[0141] The specific surface area of the negative electrode material obtained in this example is 17.9 m 2 / g. The negative electrode material was measured to have 56% mesopores and 44% micropores by nitrogen adsorption method; the mass percentage of silicon in the negative electrode material was measured to be 45.1% by sulfur-carbon analyzer.
[0142] Example 10
[0143] The porous carbon (pore size D50: 410nm, specific surface area: 493m 2 / g) was placed in a tube furnace, with an argon flow rate of 0.5L / min, and chlorosilane was introduced to deposit a silicon layer, with a silicon source flow rate of 0.15L / min; the deposition temperature was 600°C, and the deposition time was 2h. After the silicon layer deposition was completed, the gas silicon source was completely removed, the temperature was raised to 700°C, acetylene was introduced to deposit a carbon layer, the carbon source flow rate was 0.1L / min, the time was 3h, and the deposition pressure was 0.3kPa. The above deposition steps were repeated 3 times.
[0144] After the carbon layer deposition is completed, the three-layer silicon-carbon material is mixed with a 3% polyacrylonitrile ethanol solution and stirred evenly for 4 hours to obtain a polyacrylonitrile-coated silicon-carbon negative electrode material.
[0145] The polyacrylonitrile-coated silicon-carbon negative electrode material is placed in a tube furnace, and chlorosilane is introduced to deposit the silicon layer. The argon gas flow rate is 0.2L / min, and the silicon source flow rate is 0.35L / min; the deposition temperature is 450°C, and the deposition time is 1h. After the silicon layer deposition is completed, wait for the gas silicon source to be completely removed, raise the temperature to 650°C, introduce ethylene to deposit the carbon layer, the carbon source flow rate is 0.25L / min, the time is 2h, and the deposition pressure is 0.4kPa. Repeat the above deposition steps twice to obtain the silicon-carbon negative electrode material.
[0146] The specific surface area of the negative electrode material obtained in this example is 10.6 m 2 / g. The negative electrode material was measured to have 18% mesopores and 82% micropores by nitrogen adsorption method; and the mass percentage of silicon in the negative electrode material was measured to be 35.5% by sulfur-carbon analyzer.
[0147] Embodiment 11
[0148] The porous carbon (pore size D50: 390m, specific surface area: 541m 2 / g) was placed in a tube furnace, the argon flow rate was 0.42L / min, tetrasilane was introduced to deposit a silicon layer, the silicon source flow rate was 0.3L / min; the deposition temperature was 700°C, and the deposition time was 1.5h. After the silicon layer deposition was completed, the gas silicon source was completely removed, the temperature was raised to 900°C, methane was introduced to deposit a carbon layer, the carbon source flow rate was 0.15L / min, the time was 4h, and the deposition pressure was 0.1kPa.
[0149] After the carbon layer deposition is completed, an inert gas is introduced to replace the gaseous carbon source, completely remove the gaseous carbon source, and lower the reaction temperature to that of silicon source gas deposition. The above steps are repeated to deposit the silicon layer and the carbon layer once to obtain a two-layer silicon-carbon negative electrode material.
[0150] The two-layer silicon-carbon negative electrode material and 0.4% carbon nanotube slurry were mixed and stirred for 4 hours to obtain a carbon nanotube-modified silicon-carbon material.
[0151] The carbon nanotube modified silicon-carbon negative electrode material was placed in a tube furnace, the argon flow rate was 0.32L / min, tetrasilane was introduced to deposit the silicon layer, the silicon source flow rate was 0.18L / min; the deposition temperature was 650°C, and the deposition time was 1.5h. After the silicon layer deposition was completed, the gas silicon source was completely removed, the temperature was raised to 900°C, methane was introduced to deposit the carbon layer, the carbon source flow rate was 0.15L / min, the time was 3h, and the deposition pressure was 0.1kPa.
[0152] After the carbon layer deposition is completed, an inert gas is introduced to replace the gaseous carbon source, completely remove the gaseous carbon source, and lower the reaction temperature to that of silicon source gas deposition. The above steps are repeated to deposit the silicon layer and the carbon layer once to obtain a two-layer silicon-carbon negative electrode material.
[0153] The specific surface area of the negative electrode material obtained in this example is 12.9 m 2 / g. The negative electrode material was measured to have 22% mesopores and 78% micropores by nitrogen adsorption method; the mass percentage of silicon in the negative electrode material was measured to be 48.9% by sulfur-carbon analyzer.
[0154] Example 12
[0155] The phosphorus-doped porous carbon (pore size D50: 505 nm, specific surface area: 322 m 2 / g) was placed in a tube furnace, chlorosilane and borane were introduced to deposit a silicon-boron layer, the argon flow rate was 0.82 L / min, the silicon source flow rate was 0.5 L / min, and the borane flow rate was 0.02 L / min; the deposition temperature was 450°C, and the deposition time was 2 hours. Silicon-carbon material S1 was obtained.
[0156] S1 was mixed with 0.4% carbon nanotube slurry and stirred for 4 hours, mixed evenly, filtered and dried to obtain carbon nanotube-modified silicon-carbon material S2.
[0157] Place S2 in a tube furnace, replace the gas, raise the temperature to 650°C, introduce ethylene for carbon layer deposition, the carbon source flow rate is 0.2L / min, the time is 4h, and the deposition pressure is 0.4kPa. Repeat the above deposition steps 6 times to obtain the silicon-carbon negative electrode material.
[0158] The specific surface area of the negative electrode material obtained in this example is 9.1 m 2 / g. Through nitrogen adsorption method, it was measured that the negative electrode material had 16.7% mesopores and 83.3% micropores; through sulfur-carbon analyzer, it was measured that the mass percentage of silicon element in the negative electrode material was 46.1%.
[0159] Comparative Example 1
[0160] The porous carbon (pore size D50: 460nm, specific surface area: 423m 2 / g) was placed in a tube furnace, the argon flow rate was 0.75L / min, chlorosilane was introduced to deposit a silicon layer, and the silicon source flow rate was 0.35L / min; the deposition temperature was 600°C, and the deposition time was 2h. After the silicon layer deposition was completed, the gas silicon source was completely removed, the temperature was raised to 700°C, acetylene was introduced to deposit a carbon layer, the carbon source flow rate was 0.24L / min, the time was 3h, and the deposition pressure was 0.3kPa, to obtain a silicon-carbon negative electrode material.
[0161] The specific surface area of the negative electrode material obtained in this comparative example is 23.6 m 2 / g. By nitrogen adsorption method, it was measured that the negative electrode material had 65.7% mesopores and 34.3% micropores; by sulfur-carbon analyzer, it was measured that the mass percentage of silicon in the negative electrode material was 35.3%.
[0162] Comparative Example 2
[0163] The porous carbon (pore size D50: 200 m, specific surface area: 905 m 2 / g) was placed in a tube furnace, chlorosilane was introduced to deposit a silicon layer, the argon flow rate was 0.4L / min, the silicon source flow rate was 0.2L / min; the deposition temperature was 450°C, and the deposition time was 2h. After the silicon layer deposition was completed, the gas silicon source was completely removed, the temperature was raised to 600°C, ethylene was introduced to deposit a carbon layer, the carbon source flow rate was 0.12L / min, the time was 4h, and the deposition pressure was 0.4kPa, and the silicon-carbon negative electrode material was obtained.
[0164] The specific surface area of the negative electrode material obtained in this comparative example is 19.4 m 2 / g. Through nitrogen adsorption method, it was measured that the negative electrode material had 51.2% mesopores and 48.8% micropores; through sulfur-carbon analyzer, it was measured that the mass percentage of silicon in the negative electrode material was 31.4%.
[0165] Test Example 1 Electrochemical Performance Test
[0166] (1) The negative electrode material particles prepared in the above Examples 1-12 and Comparative Examples 1-2, SP, CNT, CMC and SBR were prepared into a slurry in a mass ratio of 75:12:3:5:5, coated on an 8 μm copper foil, dried in a forced air oven at 60°C for 2 h, and then several electrode sheets with a diameter of 12 mm were cut and assembled into a vacuum oven at 110°C for 7 h.
[0167] (2) After baking, the cells were quickly transferred to a glove box, and a 14 mm Φ lithium metal sheet was used as the counter electrode. A single-sided ceramic diaphragm was used, and 1 mol / L LiPF6 / (EC+DMC) (volume ratio 1:1) plus 3% VC and 3% FEC was used as the electrolyte. The button cell was assembled in the gloves, and the water and oxygen content in the glove box was controlled below 0.1 ppm.
[0168] (3) The assembled batteries were subjected to charge and discharge cycle tests. The test equipment was LAND battery test system (from Wuhan Lanhe Electronics Co., Ltd.) under the following test conditions: room temperature, 0.1C and 0.02C step discharge to 5 mV in the first three weeks, 0.1C constant current charging to 1.5 V, and 0.1C / 0.1C charge and discharge cycles for 100 weeks after the fourth week.
[0169] The results are shown in Table 1.
[0170] The material specific capacity is calculated as: charged capacity / mass of negative electrode active material; the battery first week efficiency is calculated as: battery first week charge specific capacity / battery first week discharge specific capacity; battery 100 week capacity retention rate: charge specific capacity of the 100th week / charge specific capacity of the first week
[0171] Table 1 Performance test results of negative electrode materials of embodiments and comparative examples
[0172]
[0173] As can be seen from Table 1, compared with the soft-pack batteries made of the negative electrode materials provided in Comparative Examples 1 and 2, the soft-pack batteries made of the negative electrode materials provided in the embodiments of the present application have good cycle performance, significantly reduced cell expansion, and significantly reduced expansion rate of the electrode sheet in the fully charged state. The silicon-carbon negative electrode material provided in the present application reduces lithium insertion expansion and improves material stability, thereby increasing the service life of the battery and being more conducive to the use of the battery. Among them, Figure 3 The test result diagram of the cycle number-capacity retention rate of the soft-pack battery made of the negative electrode material obtained in Example 1 shows intuitively that the capacity is well maintained even after 100 cycles.
[0174] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the detailed process equipment and process flow of the present invention, but the present invention is not limited to the above-mentioned detailed material structure, process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0175] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A negative electrode material, characterized in that: It includes a porous skeleton and at least two silicon-carbon composite material units arranged in the porous skeleton; Each of the silicon-carbon composite material units comprises a silicon material layer and a carbon material layer which are sequentially connected; A modified layer is further included between the two silicon-carbon composite material units, and the modified layer includes at least one of carbon nanotubes, graphene oxide, metal or metal alloy; The pore size D of the porous skeleton 50 =200~600nm; The method for preparing the negative electrode material comprises the following steps: (a), obtaining a porous skeleton; (b), depositing a silicon material layer; (c), depositing a carbon material layer; (d) preparing a modified layer; Repeat steps (b) and (c) at least twice.
2. The negative electrode material according to claim 1, characterized in that: Contains at least one of the following features (1) to (3): (1) The number of the silicon-carbon composite material units is 2 to 6; (2) The total thickness of all the silicon-carbon composite material units is 1 to 80 nm; (3) The mass fraction of silicon in the silicon-carbon composite material unit is 1% to 60%.
3. The negative electrode material according to claim 1, characterized in that: Contains at least one of the following features (1) to (5): (1) The specific surface area of the porous skeleton is 100 to 1500 m 2 / g; (2) The porous skeleton comprises at least one of porous carbon, porous ceramic, porous metal or alloys thereof; (3) The porous skeleton further includes a doping element, wherein the doping element includes at least one of nitrogen, phosphorus, silicon, germanium, tin, boron, aluminum, boron, gallium, and indium; (4) The porosity of the porous skeleton is 10% to 90%; (5) The particle size D of the porous skeleton 50 =2~40μm.
4. The negative electrode material according to claim 1, characterized in that It is characterized in that The thickness of the modified layer is 0.2-10 nm.
5. The negative electrode material according to claim 1, characterized in that: The silicon material layer includes at least one of elemental silicon, silicon-boron material, silicon-carbon material and silicon-oxygen material; and / or; The carbon material layer is obtained by vapor deposition using a gaseous carbon source.
6. The negative electrode material according to claim 1, characterized in that It is characterized in that The outermost layer of the negative electrode material is also provided with a porous carbon coating layer.
7. The negative electrode material according to claim 6, characterized in that: The porosity of the porous carbon coating layer is 1% to 20%; And / or, the porous carbon coating layer has a thickness of 0.1 to 3 μm.
8. The negative electrode material according to claim 1, characterized in that The method comprises at least one of the following features (1) to (11): (1) Repeat steps (b) and (c) 2 to 5 times; (2) repeating step (b), step (c) and step (d) 2 to 5 times; (3) After the last deposition of the silicon-carbon composite material unit, the method further comprises: (e) depositing a porous carbon coating layer; (4) In step (b), the gaseous silicon source for depositing the silicon material layer includes at least one of monosilane, disilane, trichlorosilane, silicon tetrafluoride, silicon tetrachloride and dichlorosilane; (5) In step (b), the deposition temperature of the silicon material layer is 400 to 900° C.; (6) In step (b), the deposition time of the silicon material layer is 0.5 to 50 hours; (7) In step (b), the flow rate of the gaseous silicon source is 0.02 to 20 L / min; (8) In step (b), the deposition pressure of the silicon material layer is 0.1 to 5 MPa; (9) In step (c), the gaseous carbon source for depositing the carbon material layer comprises at least one of ethylene, methane, ethane, propane, acetylene and ethylene; (10) In step (c), the deposition temperature of the carbon material layer is 400 to 1500° C.; (11) In step (c), the deposition time of the carbon material layer is 1 to 20 hours.
9. A negative electrode plate, characterized in that: The negative electrode material comprises the negative electrode material as described in any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Silicon carbon composite microsphere, and preparation method and application thereof
CN106384825A
A preparation method of silicon-carbon composite material for negative electrode of lithium ion battery
CN109244377A
Negative electrode material and preparation method thereof, battery and electronic equipment
CN115132997A